Ultrasound-Guided Ankle Block for Forefoot Surgery: The Contribution of the Saphenous Nerve. Issue 5 (1st September 2012) - López, Ana M.; Sala-Blanch, Xavier; Magaldi, Marta; Poggio, Daniel; Asuncion, Jordi; Franco, Carlo D.
Abstract : Background: Ankle blocks typically include the block of 5 nerves, the 4 branches that trace their origin back to the sciatic nerve plus the saphenous nerve (SaN). The sensory area of the SaN in the foot is variable. Based on our clinical experience, we decided to study the sensory distribution of the SaN in the foot and determine whether the block of this nerve is necessary as a component of an ultrasound-guided ankle block for bunion surgery. Methods: One hundred patients scheduled for bunion surgery under ankle block were prospectively studied. We performed ultrasound-guided individual blocks of the tibial, deep peroneal, superficial peroneal, and sural nerves. After obtaining complete sensory block of these nerves, we mapped the SaN sensory territory as such area without anesthesia on the medial side of the foot. Results: Every nerve block was successful within 10 minutes of injection. The saphenous territory extended into the foot to 57 ± 13 mm distal to the medial malleolus. This distal margin was 22 ± 11 mm proximal to the first tarsometatarsal joint. The proximal end of the surgical incision was located 1 cm distal to the first tarsometatarsal joint. In only 3 patients (3%), the area of SaN innervation reached the proximal end of the planned incision. Conclusions: Ultrasound-guided ankle block is a highly effective technique for bunion surgery. The sensory territory of the SaN in the foot seems to extend only to the midfoot. According to our sample, 97% of the patients undergoing bunion surgery under an ankle block would not benefit from having a SaN block.